Glass Half Full: Civic Space and Contestation in Bangladesh, Sri Lanka and Nepal - and Surie, Mandakini D.; Saluja, Sumaya; Nixon, Nicola (The Asia Foundation, 2023)
The past decade has witnessed a surge of interest in and concern over the global trend toward democratic regression. In South Asia, regulatory and institutional frameworks have become increasingly restrictive, curbing the ability of citizens and civil society organizations to occupy and use civic spaces to organize, express themselves, and participate in decisions that affect the lives of people whose interests they serve. Of course, this is only one half of the story. The other half is how citizens, collectives, and organizations adapt by carving out spaces where they can maintain—or even expand—the boundaries of their engagement in local and national civic spaces. In this paper, we examine how civic spaces are evolving in three South Asian countries—Bangladesh, Sri Lanka, and Nepal—drawing on the experiences and perspectives of civil society representatives. The paper concludes with recommendations for donors and development practitioners on how they can make relevant investments that will strengthen civic spaces and support democratic resilience in the region.